Mucoepidermoid carcinoma of the salivary glands in Brazil: clinicopathological outcomes and a brief review - Lucinei Roberto Oliveira (Revista Cubana de Estomatología, 2012)
The biological features and the clinical behavior of the mucoepidermoid carcinoma are varied and not known yet. The aim of present paper was to analyze the potential prognostic factors affecting the survival of patients diagnosed with primary mucoepidermoid carcinoma of head and neck. A retrospective study was conducted in 16 patients treated between 1990 and 2008 in the General Hospital of Riberirao Preto, USP Medicine School, Brazil. The following variables were studied: age, sex, anatomical location, tumor size, clinical stage, histological degree, relapse, metastasis, involved surgical edges ant treatment on the clinicalpathological results. The survival curves were designed using the Kaplan-Meier method and the statistic analysis was made using the log-rank test. The 68.7 % of patients was of male sex, all patients were between 13 and 83 years old. The 75 % of tumors was located in the great salivary glands, the 56.3 % in the parotid glands ones, the mucoepidermoid carcinomas of low degree and of II stage were the 37.5 %. The surgical resection was carried out in all patients. The follow-up period in present study fluctuates between 6 and 217 months. The general rate of 5- y years or 10-years survival was of 85.6 % whereas the rates of disease-free survival were of 81.8 % at 5 years and of 68.2 % at 10 years. The were statistically significant influences of the tumor size (p= 0.05), presence of metastasis (p= 0.04) and of the primary anatomical location (p= 0.04) on the rates of disease-free survival. The results obtained show the significance of the primary anatomical location of the tumor, of its size and of the presence of metastasis in the survival of mucoepidermoid carcinomas.